Fipronil prevents transmission of Lyme disease spirochetes - Radek Šíma; Adéla Palusová; Tereza Hatalová; Luise Robbertse; Petra Berková; Martin Moos; Petr Kopáček; Veronika Urbanová; Jan Perner; Ala Tabor (Parasitology)
Lyme disease, a tick-borne illness caused by Borrelia spirochetes, poses a significant threat to public health. While acaricides effectively control ticks on pets and livestock, their impact on pathogen transmission is often unclear. This study investigated the acaricidal efficacy of fipronil against Ixodes ricinus ticks and its potential to block Borrelia afzelii transmission. Initially, we employed the ex vivo membrane blood-feeding system to assess the dose–response acaricidal activity of ivermectin, fipronil and its metabolite fipronil sulfone, when supplemented in the blood meal throughout tick feeding. To obtain the temporal resolution of their acaricidal activity, ticks were allowed to initiate blood feeding on an artificial membrane before being exposed to a 1-time topical application of these acaricides. Fipronil demonstrated superior speed of acaricidal activity, with onset of tick moribundity within a few hours, prompting its selection for further in vivo testing with Borrelia-infected ticks. The I. ricinus nymphs infected with B. afzelii were topically treated with fipronil shortly after attachment to mice. Four weeks post-feeding, the skin and internal organs were examined for the presence of Borrelia. No spirochetes were detected in any organ of mice exposed to fipronil-treated ticks, while 9 out of 10 control mice, exposed to non-treated infectious ticks, displayed Borrelia infection. The in vitro co-culture experiments confirmed that fipronil had no direct effect on Borrelia viability, indicating a tick-directed effect. Overall, these results underline the potential of fipronil as a valuable tool for tick control strategies and suggest a concept for acaricide-mediated Borrelia-transmission blockers.